2020
DOI: 10.1093/schizbullopen/sgaa006
|View full text |Cite
|
Sign up to set email alerts
|

Distress Related to Attenuated Psychotic Symptoms: Static and Dynamic Association With Transition to Psychosis, Nonremission, and Transdiagnostic Symptomatology in Clinical High-Risk Patients in an International Intervention Trial

Abstract: This study examined whether distress in relation to attenuated psychotic symptoms (DAPS) is associated with clinical outcomes in an ultra-high-risk (UHR) for psychosis sample. We also investigated whether DAPS is associated with cognitive style (attributional style and cognitive biases) and whether amount of psychosocial treatment provided is associated with reduction in DAPS. The study was a secondary analysis of the ‘Neurapro’ clinical trial of omega-3 fatty acids. 304 UHR patients were recruited across ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…A major strength of this study is the empirical approach to the feature selection process, which also leverages longitudinal information in evaluating likelihood of achieving later clinical outcomes. Previous studies also showed an increase in discrimination between converters and nonconverters with joint modeling compared with baseline models [19][20][21] ; however, contrary to these studies, which rely only on baseline information to select longitudinal variables, this approach forecasts longitudinal outcomes with short-term longitudinal data in addition to baseline data. In addition, in examining both conversion to psychosis and symptom remission in parallel, we shed light on the distinctive presentations and progressions of each of these groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A major strength of this study is the empirical approach to the feature selection process, which also leverages longitudinal information in evaluating likelihood of achieving later clinical outcomes. Previous studies also showed an increase in discrimination between converters and nonconverters with joint modeling compared with baseline models [19][20][21] ; however, contrary to these studies, which rely only on baseline information to select longitudinal variables, this approach forecasts longitudinal outcomes with short-term longitudinal data in addition to baseline data. In addition, in examining both conversion to psychosis and symptom remission in parallel, we shed light on the distinctive presentations and progressions of each of these groups.…”
Section: Discussionmentioning
confidence: 97%
“…In the CHR-P population, a handful of studies using this approach have shown how change in predictor variables can inform risk of transition to psychosis . For example, continued high levels of distress associated with attenuated psychotic symptoms were found to improve prediction of conversion, but this and the other available joint models remain to be validated. While these initial findings are promising for the feasibility of implementing joint modeling within the CHR-P population, they did not identify the longitudinally changing features most useful for prediction, instead relying on change in features selected for the baseline model, and did not examine differential patterns of short-term clinical change among those who convert vs remit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings have important clinical implications. Nelson et al (2020) found that ARMS clients who are more distressed by their attenuated psychotic symptoms (DAPS) have a poorer clinical trajectory transdiagnostically and greater compromised functioning. An increase in self‐compassion was associated with a decrease in DAPS.…”
Section: Discussionmentioning
confidence: 99%
“…The trial's methodology and clinical outcomes have been described in detail elsewhere (Markulev et al, 2015;McGorry et al, 2017;Nelson et al, 2018). The main results of the Neurapro study indicated no differences in transition rates, symptomatology and functioning between the PUFAs and Placebo groups at month-12 (McGorry et al, 2017;Polari et al, 2018b) and at medium-term follow-up (Nelson et al, 2018), allowing for the pooling of the two treatment groups for the purpose of the current study, an approach that has been used elsewhere (Berger et al, 2019;Hartmann et al, 2017Hartmann et al, , 2020Nelson et al, 2020).…”
Section: Design and Settingmentioning
confidence: 97%